2020
DOI: 10.1093/icesjms/fsaa235
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic effects on wild salmon populations from stock enhancement

Abstract: Many salmonid populations are of conservation concern, and the release of hatchery-produced juveniles is a frequently used measure to alleviate declines and increase harvest opportunities. While such releases may be of conservation value for some populations, stocking may also decrease the effective population size and subsequently impose additional strain on already threatened populations. In this study, we assessed how the cohort-wise effective number of breeders in five populations of Atlantic salmon (Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…and ensuring that all hatchery-produced fish are traceable so that the effects of stocking can be evaluated Hagen et al, 2019;Hagen et al, 2020).…”
Section: Artificial Stocking Of Natural Populations To Augment Abundancementioning
confidence: 99%
“…and ensuring that all hatchery-produced fish are traceable so that the effects of stocking can be evaluated Hagen et al, 2019;Hagen et al, 2020).…”
Section: Artificial Stocking Of Natural Populations To Augment Abundancementioning
confidence: 99%
“…In the past few decades, stock enhancement has been one of the popular approaches for biodiversity conservation and fisheries management, particularly for species showing sharp declines in biomass. However, previous studies have shown that the ecological and genetic effects of hatchery releases are also of real concern because of potential negative impacts on wild populations as well as their adaptivity to varying degrees (Grant et al, 2017) [e.g., Atlantic salmon (Hagen et al, 2020), Salvelinus fontinalis (Marie et al, 2010), A. schlegelii (Shan et al, 2020)]. Although large yellow croaker has become one of the marine fish species cultured at the largest scale for hatchery release in mainland China, our results revealed no significant divergence or population structure among the JSW, ZSW, MZW, MYW, and YXW populations, while the SSBW population showed high genetic relatedness to the cultured population in terms of genetic structure and genetic diversity (Table 1, Figure 3, and Supplementary Figure 5).…”
Section: Is the Phylogeographical Pattern Of The Wild Large Yellow Croaker Population Influenced By Release Activities?mentioning
confidence: 99%
“…To recover the wild resources of large yellow croaker, large amounts of hatchery-reared juveniles have been released into the coastal waters of Fujian, Zhejiang, and Jiangsu provinces each year since 2000 (Liu, 2013). A series of previous studies have shown that stock enhancement usually has negative ecological and genetic impacts on wild populations (Grant et al, 2017;Hagen et al, 2020), such as genetic homogenization (Marie et al, 2010) and decreased genetic diversity (Shan et al, 2020). Moreover, hatchery-reared individuals may replace rather than increase the abundance of wild populations or may be harmful to other species through ecological interactions (Grant et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, long-term stock enhancement, using hatchery stocks, may cause a depletion of genetic diversity in local populations through direct replacement or genetic drift (Christie et al, 2012). Finally, restoration of wild populations with stock enhancement can reduce the Ne of the entire mixed population, based on the Ryman-Laikre effect (Hagen et al, 2021). But in this study, the S. schlegelii population had large Ne values before and after release and the confidence intervals were infinite (Pcrit = 0.05 or 0.02).…”
Section: Assessment Of the Potential Genetic Impactmentioning
confidence: 99%